2005
DOI: 10.1007/s11179-005-0047-0
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Resistant Heterotrophic Bacteria in Coastal Waters of Primorye

Abstract: Heavy metals are the major pollutants of the coastal waters of Primorye. This is associated with the natural geochemical features of the region, as well as with significant anthropogenic inputs. It is known that microorganisms are resistant actually to all heavy metals [15,20,24]. They are capable of rapid adaptation to specific habitat conditions and can thus provide an indicator of environmental changes [2,11,19]. The diversity of individual bacterial responses to toxic effects supports the plasticity of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Statistically significant differences in the minimum inhibitory concentrations of some metals were found for bacteria isolated from environments with different levels of pollution. Bacteria of the family Enterobacteriaceae and the genus Pseudomonas were the dominant metal-resistant bacterial forms in the polluted coastal wasters of Primorye (Bezverbnaya et al 2005). Positive correlations between tolerance to high levels of Cu 2+ , Pb 2+ , Zn 2+ and multi-resistant bacteria isolated from drinking water have previously been reported (Calomiris et al 1994).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Statistically significant differences in the minimum inhibitory concentrations of some metals were found for bacteria isolated from environments with different levels of pollution. Bacteria of the family Enterobacteriaceae and the genus Pseudomonas were the dominant metal-resistant bacterial forms in the polluted coastal wasters of Primorye (Bezverbnaya et al 2005). Positive correlations between tolerance to high levels of Cu 2+ , Pb 2+ , Zn 2+ and multi-resistant bacteria isolated from drinking water have previously been reported (Calomiris et al 1994).…”
Section: Discussionmentioning
confidence: 72%
“…Jana and Bhattacharya (1988) reported that several strains of members of E. coli, K. aerogene, and S. marcescens were screened for Cd resistance and sensitivity, and only one strain of each of these microorganisms was resistant to CdCl 2 . Bezverbnaya et al (2005) explained that colony-forming heterotrophic bacteria were isolated from several locations that differed in extent and character of heavy metal pollution in the coastal waters of Primorye. Statistically significant differences in the minimum inhibitory concentrations of some metals were found for bacteria isolated from environments with different levels of pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms resistant to antibiotics and tolerant to metals appear to be the result of exposure to metalcontaminated environments that cause coincidental selection for resistance factors for both [37]. Many investigators have reported that metal tolerant environmental isolates are resistant to a wide array of antibiotics and there are correlation between heavy metal resistance and antibiotic resistance [21,32,[38][39][40][41]. Metal-tolerant bacteria have evolved various resistance and detoxification mechanisms [15].…”
Section: Discussionmentioning
confidence: 99%
“…of adsorbent, solubility of the metals ions and the degree of ionization and speciation of adsorbate [24,25] . Cd, Cr, Mn and Pb adsorption increases linearly with in solution pH in the range of 7 to 10 as shown in Figure 4 for the isolated strain Bacillus sp.…”
Section: Figure 3 Phylogenetic Tree Derived From 16s Rdna Sequence Dmentioning
confidence: 99%
“…The results obtained in this study showed that the alkaline treatment is more effective in removing metals, as after 5 minutes the biosorption process removed 90% of the metals [27] . The possible reasons for this is that at pH less than 3, polymers are protonated and restrict entry of metallic ions, and at higher pH, the groups responsible for the retention of metals are negatively charged facilitating the binding of the metals ions [24,[28][29][30][31] . This resulted in a more favorable electrostatic attraction capacity of Cd, Cr, Mn and Pb: a concentration of 50 mg L -1 of metal forces, and so enhances, cationic metal ion adsorption at a temperature of 27 ± 1°C.…”
Section: Figure 3 Phylogenetic Tree Derived From 16s Rdna Sequence Dmentioning
confidence: 99%